Shape-stabilized composite phase change film with good reversible thermochromic properties fabricated via phase inversion-assisted impregnation. Issue 12 (17th February 2020) - Wang, Yuhan; Feng, Nianrong; Kang, Zhe; Wu, Dongfu; Hu, Dongying
Abstract : In this study, the composite phase-change cellulose-based film was prepared by phase inversion-assisted impregnation. Abstract : In this study, the regenerated porous cellulose film (LD) was properly prepared by dissolving cellulose in a LiCl/DMAc solvent though a simple phase inversion method. LD has a porous structure, good mechanical properties and great thermal stability. In order to form a shape-stabilized reversible thermochromic phase change film (DTLD), a reversible thermochromic compound (DTBC) was added into the LD by simple vacuum impregnation. The effect of the weight ratio of 1-dodecanol/tetradecanol complex solvent (3 : 7, 2 : 8, 1.5 : 8.5 and 1 : 9) on the phase change properties was investigated. DTLD (1.5 : 8.5) showed the highest latent heat storage of 174.00 J g −1 with the suitable phase change temperature at 37.5 °C. The low thermal conductivity of DTLD (1.5 : 8.5) at 10 °C (50 °C) was 0.396 ± 0.004 W m −1 K −1 (0.408 ± 0.002 W m −1 K −1 ). The color of DTLD (1.5 : 8.5) can change reversibly between colorless and blue as temperature changes. Melting–cooling tests after 100 cycles indicated that DTLD (1.5 : 8.5) has a high latent heat storage capacity of 169.65 J g −1 . A shape-stable reversible thermochromic phase change composite assembled from a regenerated porous cellulose membrane as a support matrix is expected to be applied to the field of thermal energy storage.